A kockázati tőkeelemek szerepe a hazai magánnyugdíjalapok portfoliójában - Kiss, Gábor Dávid (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
This study deals with the possible link between pension funds, venture capital and in-novation to manage the challenge of aging. Institutional capacities of Hungarian second pillar is engrossed by the reallocation of it’s bond and stock portfolio - therefore "exotic" investments as selected investment into the real economy by means of venture funds is uninterested. Innovative SME-s have low share on venture capital market of Visegrád countries. This is in connection with the neofordist or knowledge user profile of the subnational regions of these countries.